P07.02 Enhanced glycolysis in glioblastomas is associated with tumor cells migration. (6th September 2019) - Ndiaye, M; Rébé, C; Ilie, A; Ménégaut, L; Pilot, T; Ghiringhelli, F
Abstract: BACKGROUND: Glioblastoma is the most common primary brain tumor. Its prognosis remains poor even with the standard treatment - the Stupp protocol.The classic Warburg effect in cancers leads to increased glycolysis which causes acidification of the tumor environment. This phenomenon may favor migration of tumor cells as already reported in pancreatic ductal adenocarcinoma. We therefore hypothesized that enhanced glycolysis in glioblastomas could favor the tumor cell migration. MATERIAL AND METHODS: We measured glycolysis by the extracellular acidification rate (ECAR) of several human glioblastomas cell lines (LN229, LN18, T98-G, U87-MG, U373-MG, U118-MG) with the Seahorse Analyzer. To confirm these results, we also measured the intracellular cAMP rates using the Cayman's Elisa kit and we analyzed by RT-PCR the expression of the main genes coding for enzymes involved in glycolysis in these glioblastomas cell lines. Cell migration was measured with a scratch wound healing assay during 24 hours. RESULTS: U118-MG was the glioblastoma cell line with the highest glycolysis rate, the highest production of cAMP and showed a strong expression of glycolysis-associated genes. LN229 was the glioblastoma cell line with the less important glycolysis rate, the lower production of cAMP and showed a weaker expression of glycolysis-associated genes. According to the scratch wound healing assay, U118-MG cells showed a more important migration than LN229 cells at 24 hours. CONCLUSION: Glycolysis may be an attractive target to prevent effectively tumor cell migration in glioblastomas. Coupling the evaluation of glycolysis with histomolecular characterization of glioblastomas, could help to identify patients to whom adjuvant therapies that inhibit glycolysis such as fenofibrate could be proposed.